Development Of Technological Schemes For Transporting Rock Mass And Management Of The Working Area Of A Deep Quarry (Texas Journal of Engineering and Technology, 2025)
The operating conditions of modern industrial vehicles are determined by the increasing depth ofmining operations. This trend results in the predominant use of vehicles (over 60%) as assembly units,concentrating vehicle traffic in the working area of deep quarries with their limited space of the Muruntaudeep quarry is characterized by a high concentration of traffic, heterogeneity of the transported rock mass,and instability of key parameters. During a shift, 10-15 working faces and 5-10 transfer points are inoperation, forming over 100 routes with an average length of 3.73 km